2001
DOI: 10.1172/jci12954
|View full text |Cite
|
Sign up to set email alerts
|

Central melanocortin receptors regulate insulin action

Abstract: IntroductionInsulin resistance is regarded as the main link between obesity and type 2 diabetes mellitus (1, 2). While multiple hypotheses have been proposed to explain this association, recent discoveries on the regulation of feeding behavior and energy expenditure (3-6) have refocused attention on the potential role of hypothalamic centers in the regulation of both energy homeostasis and insulin action (Figure 1) (7-13). In fact, leptin has potent effects on glucose tolerance and insulin action, which appear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
116
4
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 150 publications
(130 citation statements)
references
References 37 publications
9
116
4
1
Order By: Relevance
“…Collectively, the data suggest a neuronal communication pathway that involves interaction between central and peripheral neuronal pancreatic MC system. The study also added further weight to previous findings that showed that dose-dependent inhibition of serum insulin in ob/ob leptin deficient mice treated centrally with a-MSH and/or synthetic MTII peptides [10,11].…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Collectively, the data suggest a neuronal communication pathway that involves interaction between central and peripheral neuronal pancreatic MC system. The study also added further weight to previous findings that showed that dose-dependent inhibition of serum insulin in ob/ob leptin deficient mice treated centrally with a-MSH and/or synthetic MTII peptides [10,11].…”
Section: Discussionmentioning
confidence: 72%
“…In addition to a key role in regulation of energy homeostasis [8], studies in wild-type, leptin deficient ob/ob mice, and in mice with diet-induced obesity showed that intracerebroventricular (icv) treatment with melanocortin peptide agonists regulates insulin action and reduces serum insulin levels [10][11][12]. For instance, a-MSH enhanced insulin actions on glucose uptake and production [11], whereas synthetic a-MSH analog MTII inhibited basal insulin secretion in a dose-dependent fashion when administered via an icv cannula [10]. These MTII findings were further solidified by observations of increased plasma insulin concentration in young lean Mc4r null mice before they were physically obese.…”
Section: Introductionmentioning
confidence: 99%
“…These rapid metabolic effects stand in sharp contrast with the insulin-sensitizing effects of prolonged activation of the central melanocortin receptors [19]. Acute ICV infusion of leptin during insulin clamp studies increases the hepatic expression of PEPCK, Glc-6-Pase, and the rate of gluconeogenesis.…”
Section: Central and Rapid Effects Of Leptin On Hepatic Glucose Fluxmentioning
confidence: 96%
“…Prolonged administration of recombinant leptin to nondiabetic and diabetic rodent models [15,16] as well as to lipodystrophic humans [17] and mice [18] markedly improves in vivo insulin action. Similarly, bidirectional modulation of the activity of the central melanocortin pathway leads to significant changes in hepatic and peripheral insulin action, independent of changes in food intake [19]. However, prolonged administration of leptin or melanocortin agonists affects the amount and distribution of body adiposity as well as lipid homeostasis, which could secondarily influence insulin sensitivity and metabolic homeostasis [15,19].…”
Section: Central and Rapid Effects Of Leptin On Hepatic Glucose Fluxmentioning
confidence: 99%
See 1 more Smart Citation